Functional Outcome of Total Hip Replacement using modified Harris Hip Score - Wod, Rupesh; Karki, Prashanna Dip; Kathayat, Tufan Singh; Gurung, Bijaya; Ghimire, Kathit Raj; Rasailee, Alisha; Pandeya, Srijana (Journal of Karnali Academy of Health Sciences, 2024)
Background: Total hip replacement (THR) is a common surgery for relieving pain and improving the quality of life in patients with moderate to severe hip arthritis. The primary reason for THR is severe hip osteoarthritis, when conservative measures fail to relieve pain. The modified Harris Hip Score (mHHS) is frequently used to assess the hip’s status before surgery and after surgery. The objective of the study was to examine functional outcomes, indications, and complications of THR using mHHS at different stages. Methods: A prospective observational study was carried out at National Trauma Center, NAMS. The study included first 35 hips of 35 patients who underwent Total Hip Replacement at our hospital and met the inclusion criteria. Follow-up assessments were conducted at 6 weeks, 3 months, and 6 months after the surgery. Each visit involved thorough clinical and radiological examinations, as well as documentation of the mHHS chart. All continuous variables were expressed as mean ± standard deviation and two sample t test was used to compare means of two sub groups. Results: The study enrolled participants aged 26 to 66, with 60% male and 40% female. Right sided involvement was observed in 55% of cases, while the left side was affected in 45%. The most common reason for surgery was osteoarthritis caused by avascular necrosis of the femoral head. The average preoperative mHHS was 28, which increased to 64 at six weeks, 86 at three months, and 92 at six months. The study found that 80% of participants achieved excellent results. Complications, including a 2.85% dislocation rate, were reported. Conclusion: THR is a safe and effective procedure, providing excellent functional outcomes and minimal complications when performed carefully and precisely. Long-term studies are needed to investigate late complications and further establish the efficacy of the implants and the procedure.